Nursing today : transition and trends - Zerwekh, JoAnn ;Garneau, Ashley Zerwekh (St. Louis, Missouri : Elsevier, Saunders, 2012)
Helps you make a successful transition from student to practicing nurse. This title covers the profession's leading issues and opportunities, ensuring that you graduate not only with patient care skills but with career development skills including resume writing, finding a job, and effective interviewing.
Unit I: Professional Growth and Transition 1. Role Transitions -- 2. Personal Management: Time and Self-Care Strategies -- 3. Mentorship and Preceptorship -- Unit II: Career Development 4. Employment Considerations: Opportunities, Resumes and Interviewing -- 5. NCLEX-RN(r) and the New Graduate -- Unit III: Nursing: A Developing Profession 6. Historical Perspectives: Influences of the Past -- 7. Nursing Education -- 8. Nursing Theories -- 9. Image of Nursing: Influences of the Present -- Unit IV: Nursing Management 10. Challenges of Nursing Management and Leadership -- 11. Building Nursing Management Skills -- 12. Effective Communication and Team Building -- 13. Conflict Management -- 14. Delegation in the Clinical Setting -- Unit V: Current Issues in Health Care -- 15. The Health Care Organization and Patterns of Nursing Care Delivery -- 16. Economics of the Health Care Delivery System -- 17. Political Action in Nursing -- 18. Collective Bargaining: Traditional (Union) and Non-Traditional Approaches -- 19. Ethical Issues -- 20. Legal Issues Unit VI: Contemporary Nursing Practice -- 21. Cultural and Spiritual Awareness -- 22. Quality Patient Care -- 23. Nursing Informatics -- 24. Using Nursing Research in Practice -- 25. Workplace Issues -- 26. Emergency Preparedness
Includes index.
Keywords: NURSING -- SOCIAL ASPECTS